EPILEPSY IN CHILD, PARTICULARITIES RELATED TO EVOLUTION AND PROGNOSIS - A CASE REPORT AND A REVIEW OF THE LITERATURE - Lorena Elena Melit; Cristina Oana Marginean; Andreea Dincă; Raluca Damian; Nicoleta Suciu; Maria Oana Mărginean (Amaltea Medical Publishing House, 2017)
Epilepsy is a brain pathology that consists in the development of recurrent epileptic seizures, and more than half of the cases present the onset during childhood. We present the case of a 3-year-old male patient, with heredocollateral antecedents of epilepsy and personal history of neuropsychomotor retardation, who was admitted in our clinic presenting generalized tonic clonic seizures, initially febrile and afterwards afebrile. The laboratory tests and the neuroimagistic ones did not identify an underlying cause. The initial EEG did not point out anything pathological. Despite the anticonvulsant treatment, the patient's evolution was unfavorable, presenting multiple short term recurrences, being readmitted multiple times in our clinic. Once we introduced the second anticonvulsant drug, levetiracetam, in his treatment, the seizures disappeared, and the patient presented long term favorable evolution. The case particularity consists in the development of generalized tonic clonic seizures in a patient with significant family history, and personal history of neuropsychomotor retardation that appear initial under febrile context, and afterwards in the lack of fever, repeating cyclic, with unfavorable evolution despite the treatment with valproic acid that disappear only after initiating treatment with levetiracetam.